Anomalous Green Luminescent Properties in CVD Synthetic Diamonds. Issue 22 (8th October 2018) - Wassell, Amber M.; McGuinness, Colin D.; Hodges, Chris; Lanigan, Peter M. P.; Fisher, David; Martineau, Philip M.; Newton, Mark E.; Lynch, Stephen A.
Abstract : In this paper, the authors explore the spectral properties of a sharp emission line centered at 499.6 nm (reported previously as 499 nm) observed in the UV‐luminescence spectrum of synthetic CVD diamond gemstones. These gemstones also exhibit spectrally prompt broad blue luminescence centered at 435 nm which is similar in character to the 425 nm blue luminescence characteristic of type IIa natural diamonds. By comparing the results against synthetic CVD diamond material which has been subjected to high temperature anneals, the authors can speculate on the nature of the defect associated with this color center. Since the 499 nm spectral line has only been observed in synthetic CVD diamonds to date, the authors further propose that it can be helpful in the identification of synthetic diamonds, in particular those showing the blue luminescence signature usually associated with type IIa natural diamonds. Abstract : Diamonds luminesce on exposure to ultraviolet light. This luminescence spectrum contains unique signatures which reveal a lot about the diamond's provenance. Recently the authors have observed an unusual long‐lived green luminescence signature in diamond gemstones that are known to be of synthetic origin. The authors discuss whether this spectral signature can be used as a tool to discriminate between natural and synthetic diamonds.